Exploratory extreme data analysis for Farmer Mac data - Husain, Qasim Nasir; Adam, Mohd Bakri; Shitan, Mahendran; Fitrianto, Anwar (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
Maximum extreme data exist in many fields. The exploration of the extreme data using exploratory data analysis approaches is still considered new although it’s being introduced four decades ago by Tukey. In this paper, proposition of some modifications of statistical techniques by Tukey focusing on the resistant line and smoothing line with running means methods are introduced. The modified of exploratory extreme data analysis gives comparable findings with the Tukey’s method and applied to extreme data set of Farmer Mac.